The effect of an external magnetic field on the maximum current of SNINS junctions near the critical temperature - Pastukh, O.Yu.; Sakhnyuk, V.E.; Svidzinsky, A.V. (Condensed Matter Physics, 2018)
The behaviour of superconducting junctions of SNINS-type (where S is superconductor, N is normal metal, I is
insulator) with anharmonic current-phase relations in the external magnetic field near the critical temperature
was investigated. The dependence of the maximum current on the value of the magnetic flux in a wide range
of electron transmission coefficient values was considered. Also, it was investigated how the presence of a
normal layer of an arbitrary thickness in the scale of coherence length and in the presence of impurities in
superconducting regions affect the sensitivity of the maximum current to the magnetic field magnitude. В роботi дослiджено поведiнку надпровiдних контактiв типу SNINS з ангармонiйною струм-фазовою залежнiстю у зовнiшньому магнiтному полi поблизу критичної температури. Проаналiзовано залежнiсть максимального струму вiд потоку зовнiшнього магнiтного поля для широкого iнтервалу змiни коефiцiєнта
проходження електронiв. Також дослiджено, як впливає на чутливiсть струму до змiни магнiтного потоку
наявнiсть нормального прошарку довiльної товщини в масштабi довжини когерентностi та наявнiсть у
надпровiдних областях немагнiтних домiшок.